Development-Oriented Countries’ Strategic Diplomacy and the 2030 Goals: A Focus on Nepal - Khadka, Bimal (NCWA Annual Journal, 2026)
Strategic diplomacy has become a key part of a country’s development path in today’s deeply interconnected and complex global society. For developing nations like Nepal, which often face economic, social, and geopolitical hurdles, strategic diplomacy is more than just a foreign policy tool; it is crucial for sustainable growth and protecting national interests. The 2030 Agenda for Sustainable Development, accepted by all United Nations Member States, serves as the global framework guiding toward peace, prosperity, and environmental balance. Aligning diplomatic efforts with these worldwide goals is vital for countries like Nepal to attract resources, forge strategic cooperation, and boost their international profile—especially as the country prepares to graduate from Least Developed Country (LDC) status in 2026. This paper explains the changing nature of development diplomacy in the Global South, highlights Nepal’s strategic responses within this framework, and explores the evolving landscape of international aid, the rise of soft power, the importance of regional and global alliances, the pathways toward achieving the Sustainable Development Goals (SDGs) 2030, and tackling climate change.